Synthesis and X-ray diffraction data of 2-morpholino-2-(3, 4, 5-trimethoxyphenyl)acetonitrile, (C15H20N2O4). Issue 2 (23rd May 2016) - Mendoza, Jose H. Quintana; Henao, J. A.; Otero, Aurora L. Carreño; Kouznetsov, Vladimir V.
Abstract : The α -aminonitrile, 2-morpholino-2-(3, 4, 5-trimethoxyphenyl)acetonitrile (C15 H20 N2 O4 ), was prepared through a silica sulfuric acid-catalyzed Strecker reaction between 3, 4, 5-trimethoxybenzaldehyde, morpholine, and two different cyanide sources. Molecular characterization was performed by Fourier transform infrared spectroscopy, gas chromatography–mass spectrometry, ( 1 H, 13 C – mono and bidimensional) nuclear magnetic resonance; crystallographic characterization was completed by X-ray powder diffraction of polycrystalline samples. The title compounds crystallized in a monoclinic system and unit-cell parameters are reported [ a = 13.904(2), b = 5.1696(6), c = 21.628(3) Å, β = 104.31(1)°, unit-cell volume V = 1506.3(3) Å 3, Z = 4]. All measured lines were indexed with the P 21 / a (No. 14) space group.